Pattern of animal bite and health care seeking behavior of victims attending a specialized hospital - Hossain, Mitali; Rashid, Mohammad Syfur; Majedul Islam, M.; Ahmed, Borhan Uddin; Abdul Karim, M.; Amin, Muhammad Kamrul (International Journal of Research in Medical Sciences, 2026)
Background: Animal bites constitute a significant yet preventable public health burden worldwide, particularly in rabies-endemic countries like Bangladesh. Despite the availability of effective post-exposure prophylaxis (PEP), gaps in awareness and timely healthcare-seeking behavior persist. The aim of the study is to assess the pattern of animal bites and the healthcare-seeking behavior of bite victims attending a specialized infectious disease hospital in Dhaka, Bangladesh. Methods: This cross-sectional study was conducted at the Infectious Diseases Hospital (IDH), Mohakhali, Dhaka, from January to December 2022. A total of 115 animal bite victims were selected through convenience sampling. Results: The mean age of participants was 33.6±15.3 years, with males constituting 72.2%. Most victims (80%) were urban residents, and 60% were married. Dogs were responsible for 73.0% of bites, followed by cats (25.2%), with stray animals accounting for 62.6% of cases. Knowledge about rabies was reported by 61.7% of participants, significantly associated with higher education level (p=0.007) and urban residence (p=0.001). Most participants (90.6%) washed wounds immediately, while economic (10.4%) and transportation (4.3%) barriers were minimal. Conclusions: Animal bites remain a substantial public health concern in Bangladesh, predominantly caused by stray dogs in urban areas. Although most victims sought timely medical care and exhibited good preventive practices, knowledge gaps and inconsistent health-seeking behaviors persist among rural and less-educated populations. Strengthening community awareness, promoting responsible pet ownership, and ensuring equitable access to rabies vaccination services are vital for achieving Bangladesh’s goal of dog-mediated rabies elimination by 2030.